Assessment of Post-Dengue Rheumatic Symptoms Using the WOMAC and DAS-28 Questionnaires in a Honduran Population after a Four-Month Follow-Up - Lysien I. Zambrano; Itzel Carolina Fuentes-Barahona; Ricardo Portillo-Pineda; Melissa Aguilar-Ponce; José Carlos Murillo-Padilla; Marlen Suazo-Menocal; Cesar Antunez-Salgado; Edissa Medina-Bassilet; Fausto Muñoz-Lara; D. Katterine Bonilla-Aldana; Juan J. Montenegro-Idrogo; Alfonso J. Rodríguez-Morales (Tropical Medicine and Infectious Disease, 2022)
Introduction: Alphaviruses may cause arthritis, but there is a lack of studies assessing it in flaviviruses such as dengue. Through the 28 Joint Disease Activity Score (DAS-28), incorporating swollen joint counts, and through the Arthritis Index from Western Ontario and McMaster Universities (WOMAC), we assessed pain, stiffness, and dimensions of arthritic function in post-DENV patients. Methods: Prospective study of a cohort of participants who were diagnosed with dengue in centres in Honduras from December 2019 to February 2020, with a follow-up period of 4 months to evaluate post-dengue rheumatological disease through the WOMAC and DAS-28 questionnaires. Results: After a four-month follow-up phase with 281 participants, the final cohort comprised 58.8% women and 41.20% men. After the follow-up, 63.02% persisted with the clinical findings. According to WOMAC, joint involvement was higher in women with (58.76%) (p < 0.0001) these symptoms or functional limitations when performing daily activities were limited to pain when walking (34.81% vs. 5.51%), climbing or descending stairs (36.46% vs. 8.66%), and at night at bedtime (28.73% vs. 7.08%). With the DAS-28, we found at least one alteration with inflammation or pain in 14.91% of the participants, primarily women (p < 0.01). Discussion: Joint involvement was high during the dengue epidemic in 2019. We observed a significant proportion of women with inflammation and joint pain, showing that dengue may lead to the development of chronic rheumatological findings, although lower than in CHIKV, still affecting everyday life and, consequently, their quality of life. Additional long-term evaluation studies after dengue are required.